The Contribution of E-Commerce and Financial Manage-ment to Enhancing MSME Performance in Indonesia - Rafida Khairani; Tantri Octora Dwi Syah Putri (Journal of Business Integration Competitive, 2025)
This study explores how e-commerce adoption and financial management jointly enhance the performance and sustainability of micro, small, and medium enterprises (MSMEs) in Indonesia. Using a qualitative literature review approach, the research identifies e-commerce as a driver of market expansion and innovation, while financial management ensures business stability and accountability. The findings show that digital transformation must be supported by financial discipline to achieve long-term growth. MSMEs that integrate both capabilities become more resilient, efficient, and competitive in the digital economy. Strengthening infrastructure, financial literacy, and collaboration among government, financial institutions, and digital platforms is essential for inclusive MSME development. Overall, the synergy between e-commerce and financial management provides a strategic foundation for building sustainable and competitive MSMEs in Indonesia’s evolving digital landscape.